Depletion of CD11c+ cells in the CD11c.DTR model drives expansion of unique CD64+ Ly6C+ monocytes that are poised to release TNF‐α. Issue 1 (30th November 2015) - Sivakumaran, Shivajanani; Henderson, Stephen; Ward, Sophie; Santos E. Sousa, Pedro; Manzo, Teresa; Zhang, Lei; Conlan, Thomas; Means, Terry K.; D'Aveni, Maud; Hermine, Olivier; Rubio, Marie‐Thérèse; Chakraverty, Ronjon; et al.
Abstract : Dendritic cells (DCs) play a vital role in innate and adaptive immunities. Inducible depletion of CD11c + DCs engineered to express a high‐affinity diphtheria toxin receptor has been a powerful tool to dissect DC function in vivo. However, despite reports showing that loss of DCs induces transient monocytosis, the monocyte population that emerges and the potential impact of monocytes on studies of DC function have not been investigated. We found that depletion of CD11c + cells from CD11c.DTR mice induced the expansion of a variant CD64 + Ly6C + monocyte population in the spleen and blood that was distinct from conventional monocytes. Expansion of CD64 + Ly6C + monocytes was independent of mobilization from the BM via CCR2 but required the cytokine, G‐CSF. Indeed, this population was also expanded upon exposure to exogenous G‐CSF in the absence of DC depletion. CD64 + Ly6C + monocytes were characterized by upregulation of innate signaling apparatus despite the absence of inflammation, and an increased capacity to produce TNF‐α following LPS stimulation. Thus, depletion of CD11c + cells induces expansion of a unique CD64 + Ly6C + monocyte population poised to synthesize TNF‐α. This finding will require consideration in experiments using depletion strategies to test the role of CD11c + DCs in immunity.